Trends, Challenges, and Opportunities in the Integration of 21st Century Skills into Exit Exams: A Systematic Literature Review - Teshome, Samson Worku (International Journal of Education, Management, and Technology, 2025)
This systematic literature review explores the intersection of exit exams and 21st century skills, focusing on how exit exams are being adapted to assess competencies such as critical thinking, creativity, collaboration, communication, digital literacy, and problem-solving. The review follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and employs the PICO (Population, Intervention, Comparison, Outcome) framework to structure the research question and guide the search strategy. A comprehensive search of electronic databases and manual searches yielded 15 studies, which were analyzed to identify trends, challenges, and opportunities in the integration of 21st century skills into exit exams. The findings reveal that while exit exams have traditionally focused on academic achievement, there is growing interest in adapting them to measure 21st century skills. However, significant challenges remain, including the difficulty of assessing non-cognitive skills, potential unintended consequences such as increased student stress, and the need for innovative assessment methods. The review highlights the potential of online exams and performance-based tasks to provide more inclusive and flexible assessments. Overall, this review underscores the importance of aligning exit exams with the demands of the modern workforce and calls for further research to develop effective and equitable assessment methods for 21st century skills.